Fault Detection Approaches to Power System: State-of-the-Art Article Reviews for Searching a New Approach in the Future - Pituk Bunnoon (Institute of Advanced Engineering and Science, 2013)
This paper proposes the state-of-the-art of fault detection approach a power system. Severalarticles presented it in each implementation and method from the last to present (2013). Theadvantage of the approach would be developed to the new detection in the future. Manyinterested topics used for detection of fault in the power system. In this research can beclassified into two types interesting in fault detection. This review of many paper will beused to develop the research or find the new method for an appropriate fault detection in thepower system.DOI:http://dx.doi.org/10.11591/ijece.v3i4.3195